Effect of aramid fibres and fly ash cenosphere on PVA-ECC properties - Koh, Benjamin Ye Bin (2018)
Fire resistance is one of the important material properties for concrete materials, which could mean the difference between life and death in the event of fire disasters. This is especially so in an enclosed environment like within a building or a concrete tunnel where one has only moments to react and get to safety. Therefore, the objective of this study is to examine Engineered Cementitious Composites (ECC) with a hybrid mixture of fibres to determine the optimal mix design which will improve its fire resistance and its mechanical properties. The two main fibres chosen were Polyvinyl Alcohol (PVA) fibres and Aramid fibres which are to be included into the concrete matrix. The Taguchi method, which is a statistical method, was adopted in the formulation of the mix table. The mix design table was formulated with reference to a series of trial mixes which were based of a previous research (Huang, X., Ranade, R., Zhang, Q., Ni, W., & Li, V. C., 2013) [1]. Besides the fibres in focus, the mix design consists of: • Ordinary Portland Cement (OPC) • Fly Ash (FA) • Fly Ash Cenosphere (FAC) • Water (H2O) • Superplasticizer (SP) • Air-entraining Agent (AEA) These ingredients are added in varying quantities and is determined by a variety of ratios. These include: • Fly ash to cement ratio, which make up the binder (FA + OPC) • FAC to binder ratio • H2O to binder ratio • SP to binder ratio. The fibres are added as a percentage of the total mix volume. A total of 2 three level Taguchi design [L9, 34] series was conducted on the chosen materials. The resultant 18 mix designs were casted in the laboratory as dog bone and cubic samples to be tested in tension and compression respectively.